Comparison of Radiofrequency Ablation Versus Cryoablation For T1 Renal Tumors: An Evidence-Based Analysis of Comparative Outcomes - Shi, Hongjin; Li, Jinze; Fan, Zhinan; Yang, Jing; Fu, Shi; Wang, Haifeng; Wang, Jiansong; Zhang, Jinsong (Frontiers in Oncology, 2022)
Objective: To discuss the differences in the effectiveness and security for T1 renal tumors by radiofrequency ablation (RFA) and cryoablation (CA). Methods: We systematically searched the Cochrane Library, PubMed, Embase, CNKI databases, and Science databases, and the date was from the above database establishment to August 2021. Controlled trials on RFA and CA for T1 renal tumors were included. The meta-analysis was conducted with the Review Manager 5.4 software. Results: A total of ten studies with 2,367 patients were included in the analysis. There were no significant differences in complications (odds ratio [OR], 1.23; 95% CI, 0.80 to 1.90; p=0.35), primary technique efficacy rate (OR, 1.01; 95% CI, 0.33 to 3.14; p=0.98), changes in serum creatinine (weighted mean difference [WMD], 0.53; 95% CI, -0.50 to 1.57; p=0.31), or 5-year survival rate (hazard ratio [HR], 1.11; 95% CI, 0.41 to 3.00; p=0.84) among patients undergoing RFA and CA . However, compared with patients who underwent RFA, patients who underwent CA had a lower Local recurrence (OR: 2.25; 95% CI: 1.38 to 3.67; p = 0.001). Conclusion: The analysis demonstrated that in the treatment of T1 renal tumors, CA was clinically superior to RFA in controlling local tumor recurrence. However, no differences were observed in terms of primary technique efficacy rate，5-year survival rate, changes in serum creatinine，and complication rate between groups.